Insitu grown Ni9S8 nanorod/O-MoS2 nanosheet nanocomposite on carbon cloth as a free binder supercapacitor electrode and hydrogen evolution catalyst. (10th October 2017) - Li, Songzhan; Chen, Tian; Wen, Jian; Gui, Pengbin; Fang, Guojia
Abstract: Transition metal sulfide nanostructure composites have received significant attention as energy conversion and storage devices. In this work, we report a three-dimension (3D) nanostructure with the Ni9 S8 nanorods embedded in oxygen-incorporated MoS2 (O-MoS2 ) nanosheets for supercapacitors and hydrogen evolution catalysts. The in situ grown Ni9 S8 /O-MoS2 nanocomposite on carbon cloth can be used as a free binder supercapacitor electrode and hydrogen evolution catalyst. The Ni9 S8 /O-MoS2 nanocomposite exhibits electrochemical behaviors with a specific capacitance of 907 F g −1 (at 2 A g −1 ) and good cycle stability after 1200 cycles due to its unique mutual embedding 3D nanostructure. Furthermore, the Ni9 S8 /O-MoS2 nanocomposite also shows highly electrocatalytic features for hydrogen production with an onset overpotential of ∼150 mV and a low Tafel slope of ∼81 mV dec −1 . The oxygen incorporation of MoS2 provides more active sites to participate in the catalytic process for the hydrogen evolution reaction.